STRUCTURE AND VARIABILITY OF DEEP WATERS IN THE ROMANCHE FRACTURE ZONE - Demidov A.N.; Morozov E.G.; Neiman V.G. (My University, 2006)
Hydrophysical measurements in the Romanche Fracture Zone carried out in October 2005 were compared to the data of measurements in 1991. As a result, warming by 0.01°C was found in the core of North Atlantic Deep Water (NADW), and warming by 0.034 °C was recorded in the layer of Antarctic Bottom Water (AABW). Our results confirmed the conclusions of Mantyla and Reid, according to which the major part of AABW passes to the Northeast Atlantic not through the Romanche Fracture Zone but through the Vema Fracture Zone at 11° N.